Surgical Management of Mucocele by Using Diode Laser: Two Case Reports - Srinivasa, T. S; Farista, Sana; Agrawal, Parul; Jain, Priya; Deonani, Sushmita; Goswami, Varsha (International Journal of Occupational Safety and Health, 2015)
Mucoceles are benign, mucus-containing cystic lesions of the minor salivary glands. They are not true cysts since most of them lack an epithelial lining. These lesion occur most commonly in the lower lip. This case report presents two cases of mucocele on the lower and upper lips. This lesion was diagnosed based on history, clinical finding and histopathological examination. The excision of the lesion was planed using diode laser. After re-evaluation of both the patients healing was satisfactory. DOI: http://dx.doi.org/10.3126/ijosh.v4i1.12167